Expansion and Molecular Characterization of AP2/ERF Gene Family in Wheat (Triticum aestivum L.) - Riaz, Muhammad Waheed; Lu, Jie; Shah, Liaqat; Yang, Liu; Chen, Can; Mei, Xu Dong; Xue, Liu; Manzoor, Muhammad Aamir; Abdullah, Muhammad; Rehman, Shamsur; Si, Hongqi; Ma, Chuanxi (Frontiers in Genetics, 2021)
The AP2/ERF is a large protein family of transcription factors, playing an important role in signal transduction, plant growth, development, and response to various stresses. AP2/ERF super-family is identified and functionalized in a different plant but no comprehensive and systematic analysis in wheat (Triticum aestivum L.) has been reported. However, a genome-wide and functional analysis was performed and identified 322 TaAP2/ERF putative genes from the wheat genome. According to the phylogenetic and structural analysis, TaAP2/ERF genes were divided into 12 subfamilies (Ⅰa, Ⅰb, Ⅰc, Ⅱa, Ⅱb, Ⅱc, Ⅲa, Ⅲb, Ⅲc, Ⅳa, Ⅳb, Ⅳc). Furthermore, conserved motifs and introns/exons analysis revealed may lead to functional divergence within clades. Cis- Acting analysis indicated that many elements were involved in stress-related and plant development. Chromosomal location showed that 320 AP2/ERF genes were distributed among 21 chromosomes and 2 genes were present in a scaffold. Interspecies microsynteny analysis revealed that maximum orthologous between Arabidopsis, rice followed by wheat. Segment duplication events have contributed to the expansion of the AP2/ERF family and made this family larger than rice and Arabidopsis. Additionally, AP2/ERF genes were differentially expressed in wheat seedlings under the stress treatments of heat, salt, and drought, and expression profiles were verified by qRT-PCR. Remarkably, the RNA-seq data exposed that AP2/ERF gene family might play a vital role in stress-related. Taken together, our findings provided useful and helpful information to understand the molecular mechanism and evolution of the AP2/ERF gene family in wheat.